Pemeriksaan Kesehatan Gratis Bagi Warga Toddopuli Bersama Klinik MEDIKA FARMA - Anurogo, Dito; Musiana, Musiana; Rahmat, Rezqiqah Aulia; Rusli, Rusli; Sulfiani, Sulfiani; Marpaung, Mauritz Pandapotan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Health is a condition that is not only free from disease but also includes all aspects of human life which includes physical, emotional, social and spiritual aspects. The purpose of this activity is to provide basic health information to the community about physical examinations, as well as provide counseling based on the results of health checks so that the realization of a healthy community to the community. So that if results are found that are not within normal limits, education can be given directly to regulate lifestyle and advised to consult the nearest doctor. If we can find out the abnormal process in the body as soon as possible, complications with the disease can be avoided as early as possible. For the implementation of PKM activities carried out at the Medika Farma Clinic which was held on September 21, 2023.